On the filtering of intersegmental loads during running - Edwards, W. B.; Troy, K. L.; Derrick, T. R. (Gait and Posture, 2011)
When performing inverse dynamics analysis, smoothing kinematic and force platform data at different cutoff frequencies creates an "impact" like artifact that is visible in the joint moments during impulsive activity. Here we illustrate a processing technique in which inverse dynamics analysis is performed on the raw kinematic and force platform data and the joint reaction forces and moments are subsequently smoothed based on the frequency content of the distal reaction force. The effectiveness of this technique is illustrated on forward dynamics simulation data with known intersegmental loads. We then apply the technique to an experimental data set of 10 subjects running at three prescribed speeds. We show that performing inverse dynamics on the raw data and subsequently smoothing the intersegmental loads results in minimal attenuation of the joint reaction force and avoids impact artifacts in the joint moments. Artifacts that occur using a traditional filtering technique are systematic, become more pronounced with speed, and are most noticeable at the hip joint.